1989
DOI: 10.1111/j.1365-2648.1989.tb01480.x
|View full text |Cite
|
Sign up to set email alerts
|

Staff nurses' attitudes toward nursing research: a descriptive survey

Abstract: Staff nurse involvement in clinical nursing research is dependent on the attitudes nurses hold toward research. An exploration of these attitudes was undertaken in a 464-bed midwestern teaching hospital as it developed its nursing research procedures. A questionnaire was developed which incorporated the Boothe Attitudes on Nursing Research Scale. All registered nurses (n = 925) at the facility were surveyed with a response rate of 77.8% (n = 720). Findings indicated that many nurses were interested in research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0
5

Year Published

1993
1993
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 17 publications
2
28
0
5
Order By: Relevance
“…The data support quantitative work that shows graduate nurses hold positive views towards research (Bostrom et al, 1989;Champion and Leach, 1989;Nilsson et al, 1998). However, this qualitative study reveals further understandings, with participants reporting being particularly motivated when a research proposal was perceived as relevant to their practice.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The data support quantitative work that shows graduate nurses hold positive views towards research (Bostrom et al, 1989;Champion and Leach, 1989;Nilsson et al, 1998). However, this qualitative study reveals further understandings, with participants reporting being particularly motivated when a research proposal was perceived as relevant to their practice.…”
Section: Discussionsupporting
confidence: 85%
“…Accordingly, research theory is being increasingly established in contemporary pre-registration and higher nurse education courses in the UK (Hek and Shaw, 2006). Nurses with a higher level of education have been found to use research findings more frequently than their less educated colleagues (Lacey, 1994;Veeramah, 2004;Hek and Shaw, 2006); graduate nurses perceive fewer barriers to conducting research as compared with non-graduates (Bostrom et al, 1989;Champion and Leach, 1989;Nilsson et al, 1998); and an increasing focus on research in education curricula has contributed towards younger nurses implementing research (Bjorkstrom and Hamrin, 2001).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Also the attitudes of important administrators were influential. Bostrom et al (1989 ) found nurses had a positive attitude to the conducting of research in clinical practice, but they lacked knowledge of the research process and thus needed education. Bostrom & Suter (1993) found indicators that a nurse was more likely to use research results if he or she had made contributions to the research process, such as data collection.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies show that nurses who are more comfortable with research are more likely to make changes in their practice. 2,3 However, deficits in a nurse's wound care knowledge, regardless of certification status or difference in education, are not well known.…”
mentioning
confidence: 99%